ApiAP2 Transcription Factors in Apicomplexan Parasites - Jeninga, Myriam; Quinn, Jennifer; Petter, Michaela (Pathogens, 2019)
Apicomplexan parasites are protozoan organisms that are characterised by complex life cycles and they include medically important species, such as the malaria parasite Plasmodium and the causative agents of toxoplasmosis (Toxoplasma gondii) and cryptosporidiosis (Cryptosporidium spp.). Apicomplexan parasites can infect one or more hosts, in which they differentiate into several morphologically and metabolically distinct life cycle stages. These developmental transitions rely on changes in gene expression. In the last few years, the important roles of different members of the ApiAP2 transcription factor family in regulating life cycle transitions and other aspects of parasite biology have become apparent. Here, we review recent progress in our understanding of the different members of the ApiAP2 transcription factor family in apicomplexan parasites.
CRIS-Team WoS Importer:2019-07-30

Automated detection and staging of malaria parasites from cytological smears using convolutional neural networks. - Davidson, Mira S; Andradi-Brown, Clare; Yahiya, Sabrina; Chmielewski, Jill; O’Donnell, Aidan J; Gurung, Pratima; Jeninga, Myriam; Prommana, Parichat; Dean, Andrew P.; Petter, Michaela; Uthaipibull, Chairat; Boyle, Michelle J; et al. (Biological Imaging, 2021)
Microscopic examination of blood smears remains the gold standard for laboratory inspection and diagnosis of malaria. Smear inspection is, however, time-consuming and dependent on trained microscopists with results varying in accuracy. We sought to develop an automated image analysis method to improve accuracy and standardization of smear inspection that retains capacity for expert confirmation and image archiving. Here, we present a machine learning method that achieves red blood cell (RBC) detection, differentiation between infected/uninfected cells, and parasite life stage categorization from unprocessed, heterogeneous smear images. Based on a pretrained Faster Region-Based Convolutional Neural Networks (R-CNN) model for RBC detection, our model performs accurately, with an average precision of 0.99 at an intersection-over-union threshold of 0.5. Application of a residual neural network-50 model to infected cells also performs accurately, with an area under the receiver operating characteristic curve of 0.98. Finally, combining our method with a regression model successfully recapitulates intraerythrocytic developmental cycle with accurate lifecycle stage categorization. Combined with a mobile-friendly web-based interface, called PlasmoCount, our method permits rapid navigation through and review of results for quality assurance. By standardizing assessment of Giemsa smears, our method markedly improves inspection reproducibility and presents a realistic route to both routine lab and future field-based automated malaria diagnosis.
EVALuna2:519458

Plasmodium falciparum gametocytes display global chromatin remodelling during sexual differentiation - Jeninga, Myriam; Tang, Jingyi; Selvarajah, Shamista A.; Maier, Alexander G.; Duffy, Michael F.; Petter, Michaela (BMC Biology, 2023)
Background: The protozoan malaria parasite Plasmodium falciparum has a complex life cycle during which it needs to differentiate into multiple morphologically distinct life forms. A key process for transmission of the disease is the development of male and female gametocytes in the human blood, yet the mechanisms determining sexual dimorphism in these haploid, genetically identical sexual precursor cells remain largely unknown. To understand the epigenetic program underlying the differentiation of male and female gametocytes, we separated the two sexual forms by flow cytometry and performed RNAseq as well as comprehensive ChIPseq profiling of several histone variants and modifications. Results: We show that in female gametocytes the chromatin landscape is globally remodelled with respect to genome-wide patterns and combinatorial usage of histone variants and histone modifications. We identified sex specific differences in heterochromatin distribution, implicating exported proteins and ncRNAs in sex determination. Specifically in female gametocytes, the histone variants H2A.Z/H2B.Z were highly enriched in H3K9me3-associated heterochromatin. H3K27ac occupancy correlated with stage-specific gene expression, but in contrast to asexual parasites this was unlinked to H3K4me3 co-occupancy at promoters in female gametocytes. Conclusions: Collectively, we defined novel combinatorial chromatin states differentially organising the genome in gametocytes and asexual parasites and unravelled fundamental, sex-specific differences in the epigenetic code. Our chromatin maps represent an important resource for future understanding of the mechanisms driving sexual differentiation in P. falciparum.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Epigenome; Gametocytogenesis; Histone variants; Malaria; Plasmodium falciparum; Transcriptome

The Coxiella burnetii T4SS effector protein AnkG hijacks the 7SK small nuclear ribonucleoprotein complex for reprogramming host cell transcription - Cordsmeier, Arne; Rinkel, Sven; Jeninga, Myriam; Schulze-Lührmann, Jan; Oelke, Martha; Schmid, Benedikt; Hasler, Daniele; Meister, Gunter; Haecker, Georg; Petter, Michaela; Beare, Paul A.; Lührmann, Anja (PLoS Pathogens, 2022)
Inhibition of host cell apoptosis is crucial for survival and replication of several intracellular bacterial pathogens. To interfere with apoptotic pathways, some pathogens use specialized secretion systems to inject bacterial effector proteins into the host cell cytosol. One of these pathogens is the obligate intracellular bacterium Coxiella burnetii, the etiological agent of the zoonotic disease Q fever. In this study, we analyzed the molecular activity of the anti-apoptotic T4SS effector protein AnkG (CBU0781) to understand how C. burnetii manipulates host cell viability. We demonstrate by co- and RNA-immunoprecipitation that AnkG binds to the host cell DExD box RNA helicase 21 (DDX21) as well as to the host cell 7SK small nuclear ribonucleoprotein (7SK snRNP) complex, an important regulator of the positive transcription elongation factor b (P-TEFb). The co-immunoprecipitation of AnkG with DDX21 is probably mediated by salt bridges and is independent of AnkG-7SK snRNP binding, and vice versa. It is known that DDX21 facilitates the release of P-TEFb from the 7SK snRNP complex. Consistent with the documented function of released P-TEFb in RNA Pol II pause release, RNA sequencing experiments confirmed AnkG-mediated transcriptional reprogramming and showed that expression of genes involved in apoptosis, trafficking, and transcription are influenced by AnkG. Importantly, DDX21 and P-TEFb are both essential for AnkG-mediated inhibition of host cell apoptosis, emphasizing the significance of the interaction of AnkG with both, the DDX21 protein and the 7SK RNA. In line with a critical function of AnkG in pathogenesis, the AnkG deletion C. burnetii strain was severely affected in its ability to inhibit host cell apoptosis and to generate a replicative C. burnetii-containing vacuole. In conclusion, the interference with the activity of regulatory host cell RNAs mediated by a bacterial effector protein represent a novel mechanism through which C. burnetii modulates host cell transcription, thereby enhancing permissiveness to bacterial infection.
CRIS-Team Scopus Importer:2022-02-25

The exception that proves the rule: Virulence gene expression at the onset of Plasmodium falciparum blood stage infections - Wichers-Misterek, Jan Stephan; Krumkamp, Ralf; Held, Jana; von Thien, Heidrun; Wittmann, Irene; Höppner, Yannick Daniel; Ruge, Julia M.; Moser, Kara; Dara, Antoine; Strauss, Jan; Esen, Meral; Fendel, Rolf; et al. (PLoS Pathogens, 2023)
Controlled human malaria infections (CHMI) are a valuable tool to study parasite gene expression in vivo under defined conditions. In previous studies, virulence gene expression was analyzed in samples from volunteers infected with the Plasmodium falciparum (Pf) NF54 isolate, which is of African origin. Here, we provide an in-depth investigation of parasite virulence gene expression in malaria-naïve European volunteers undergoing CHMI with the genetically distinct Pf 7G8 clone, originating in Brazil. Differential expression of var genes, encoding major virulence factors of Pf, PfEMP1s, was assessed in ex vivo parasite samples as well as in parasites from the in vitro cell bank culture that was used to generate the sporozoites (SPZ) for CHMI (Sanaria PfSPZ Challenge (7G8)). We report broad activation of mainly B-type subtelomeric located var genes at the onset of a 7G8 blood stage infection in naïve volunteers, mirroring the NF54 expression study and suggesting that the expression of virulence-associated genes is generally reset during transmission from the mosquito to the human host. However, in 7G8 parasites, we additionally detected a continuously expressed single C-type variant, Pf7G8_040025600, that was most highly expressed in both pre-mosquito cell bank and volunteer samples, suggesting that 7G8, unlike NF54, maintains expression of some previously expressed var variants during transmission. This suggests that in a new host, the parasite may preferentially express the variants that previously allowed successful infection and transmission.
CRIS-Team Scopus Importer:2023-07-21

The P. falciparum alternative histones Pf H2A.Z and Pf H2B.Z are dynamically acetylated and antagonized by PfSir2 histone deacetylases at heterochromatin boundaries - Azizan, Suffian; Selvarajah, Shamista A.; Tang, Jingyi; Jeninga, Myriam; Schulz, Danae; Pareek, Kapil; Herr, Tamara; Day, Karen P.; De Koning-Ward, Tania F.; Petter, Michaela; Duffy, Michael F. (mBio, 2023)
The Plasmodium falciparum alternative histones Pf H2A.Z and Pf H2B.Z are enriched in the same nucleosomes in intergenic euchromatin but depleted from heterochromatin. They occupy most promoters but are only dynamically associated with expression at var genes. In other organisms, acetylation of H2A.Z is important for its functions in gene expression and chromatin structure. Here, we show that acetylated Pf H2A.Z and Pf H2B.Z are dynamically associated with gene expression at promoters. In addition, acetylated Pf H2A.Z and Pf H2B.Z are antagonized by the sirtuin class III histone deacetylases (HDAC) PfSir2A and B at heterochromatin boundaries and encroach upon heterochromatin in parasites lacking PfSir2A or B. However, the majority of acetylated Pf H2A.Z and Pf H2B.Z are deacetylated by class I or II HDACs. Acetylated Pf H2A.Z and Pf H2B.Z are also dynamically associated with promoter activity of both canonical upstream var gene promoters and var gene introns. These findings suggest that both acetylated Pf H2A.Z and Pf H2B.Z play critical roles in gene expression and contribute to maintenance of chromatin structure at the boundaries of subtelomeric, facultative heterochromatin, critical for the variegated expression of genes that enable rapid adaptation to altered host environments.
CRIS-Team Scopus Importer:2024-12-16
Keywords: chromatin; epigenetics; malaria; regulation of gene expression; variant histones

The Putative Bromodomain Protein PfBDP7 of the Human Malaria Parasite Plasmodium Falciparum Cooperates With PfBDP1 in the Silencing of Variant Surface Antigen Expression - Quinn, Jennifer; Jeninga, Myriam; Limm, Katharina; Pareek, Kapil; Meißgeier, Tina; Bachmann, Anna; Duffy, Michael F.; Petter, Michaela (Frontiers in Cell and Developmental Biology, 2022)
Epigenetic regulation is a critical mechanism in controlling virulence, differentiation, and survival of the human malaria parasite Plasmodium (P.) falciparum. Bromodomain proteins contribute to this process by binding to acetylated lysine residues of histones and thereby targeting the gene regulatory machinery to gene promoters. A protein complex containing the P. falciparum bromodomain proteins (PfBDP) 1 and PfBDP2 (BDP1/BDP2 core complex) was previously shown to play an essential role for the correct transcription of invasion related genes. Here, we performed a functional characterization of a third component of this complex, which we dubbed PfBDP7, because structural modelling predicted a typical bromodomain fold. We confirmed that PfBDP7 is a nuclear protein that interacts with PfBDP1 at invasion gene promoters in mature schizont stage parasites and contributes to their transcription. Although partial depletion of PfBDP7 showed no significant effect on parasite viability, conditional knock down of either PfBDP7 or PfBDP1 resulted in the de-repression of variant surface antigens (VSA), which are important pathogenicity factors. This de-repression was evident both on mRNA and protein level. To understand the underlying mechanism, we mapped the genome wide binding sites of PfBDP7 by ChIPseq and showed that in early schizonts, PfBDP7 and PfBDP1 are commonly enriched in heterochromatic regions across the gene body of all VSA families, including genes coding for PfEMP1, RIFIN, STEVOR, and PfMC-2TM. This suggests that PfBDP7 and PfBDP1 contribute to the silencing of VSAs by associating with heterochromatin. In conclusion, we identified PfBDP7 as a chromatin binding protein that is a constitutive part of the P. falciparum BDP1/BDP2 core complex and established PfBDP1 and PfBDP7 as novel players in the silencing of heterochromatin regulated virulence gene families of the malaria parasite P. falciparum.
CRIS-Team Scopus Importer:2022-05-06
Keywords: bromodomain; chromatin; malaria; P. falciparum; variant surface antigens